Comparative assessment of anti-fibrotic potential of drugs using an in vivo zebrafish model of lupus nephritis-associated fibrosis - Jepson, Tayla (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2025.